2016
DOI: 10.3389/fpls.2016.00459
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Use Efficiency Is a Significant Determinant of Drought Stress Tolerance in Relation to Photosynthetic Activity in Brassica napus Cultivars

Abstract: To investigate the varietal difference in sulfur use efficiency (SUE) and drought stress tolerance, Brassica napus ‘Mosa’ and ‘Saturnin’ were exposed to polyethylene glycol (PEG)-induced drought stress for 72 h. Direct quantification of S uptake, de novo synthesis of amino acids and proteins was performed by tracing 34S. The responses of photosynthetic activity in relation to SUE were also examined. The total amount of newly absorbed S decreased with drought stress in both cultivars but the decrease rate was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 45 publications
4
44
0
Order By: Relevance
“…Liang [ 44 ] found that drought stress increased D-alanine synthase activity in tobacco. Sulfur was found to be a significant determinant of drought stress tolerance in Brassica napus [ 45 ]. Some minerals have been shown to enhance the resistance of plants to drought stress [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang [ 44 ] found that drought stress increased D-alanine synthase activity in tobacco. Sulfur was found to be a significant determinant of drought stress tolerance in Brassica napus [ 45 ]. Some minerals have been shown to enhance the resistance of plants to drought stress [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In some species, these pathways are involved the responses to various abiotic stresses. For example, the formation of free amino acids in cotton under high temperature stress may play a significant role in maintaining cell water potential, eliminating toxicity, and storing nitrogen [ 91 ]; sulfur metabolism was found to be an important component of the cold resistance mechanism of cassava [ 92 ]; in B. napus [ 45 ], sulfur uptake affected the availability of total sulfur, which played important roles in alleviating damage caused by drought stress. Some minerals have been shown to enhance the drought tolerance of plants by increasing the concentration of antioxidants [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…High doses of K 2 SO 4 and Na 2 SO 4 (45 kg ha −1 ) showed adverse effects on biomass accumulation as reported earlier in studies involving maize 35 and Brassica rapa 36 www.nature.com/scientificreports www.nature.com/scientificreports/ Addition of sufficient amount of nutrients is first agricultural measure to increase crop performance 38 , however, the uptake of mineral nutrients is considerably influenced by the interactions between metal ions at different physiological levels 24 . This is particularly true for S as drought stress results in low SO 4 2− absorption and its subsequent translocation to leaves that also limits NO 3 − translocation, consequently reducing nitrogen use efficiency 39 . Similarly, S-deprivation influences K accumulation in shoots providing evidence that K + acts as counter-cation in the absence of SO 4 2− in leaf tissue 24,40 .…”
Section: Discussionmentioning
confidence: 99%
“…3b) suggesting that these fertilizers influence stomatal regulation and further stabilize Fe-S clusters to improve the functioning of vital cellular processes such as photosynthesis and respiration under water deficit conditions 73,74 . In a study involving contrasting B. napus genotypes (Mosa and Saturnin), Lee et al 39 reported higher photosynthetic activity in genotype (Saturnin) with high sulfur use efficiency that ultimately contributed to better drought tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged water-deficit (e.g., drought) is considered a major climatic factor limiting plant growth and development. The decrease in water availability for transport-associated processes modifies intercellular metabolites concentration, followed by the disturbance of amino acid and carbohydrate metabolism (Kim et al ., 2004; Lee et al ., 2016). An accumulation of reactive oxygen species (ROS) and/or proline is observed as a common stress response (Lee et al ., 2013; Rejeb et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%